2020
DOI: 10.1109/jphotov.2019.2954768
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Light and Elevated Temperature Induced Degradation and Surface-Related Degradation Kinetics in Float-Zone Silicon by Varying the Initial Sample State

Abstract: Light and elevated temperature induced degradation (LeTID) kinetics in float-zone silicon are investigated by varying the initial sample state, composed of different base material, base doping, SiN x :H films, and subsequent firing, and/or annealing steps. The approach of deliberately changing the initial sample state is shown to allow for specific studies of influences of LeTID kinetics. Bulk-and surface-related degradations are examined separately and the influence on the kinetics of bulk-and surface-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
(61 reference statements)
1
9
0
Order By: Relevance
“…The sinks that are best controlled in silicon wafer processing are the dopant atoms. In a recent study, Hammann et al [50] demonstrated that in otherwise similarly processed p-type FZ samples with different base resistivity, the maximum [LD] was much larger for samples with higher doping. This observation can directly be explained by our theory.…”
Section: Discussionmentioning
confidence: 99%
“…The sinks that are best controlled in silicon wafer processing are the dopant atoms. In a recent study, Hammann et al [50] demonstrated that in otherwise similarly processed p-type FZ samples with different base resistivity, the maximum [LD] was much larger for samples with higher doping. This observation can directly be explained by our theory.…”
Section: Discussionmentioning
confidence: 99%
“…These defects are found to be activated by heat-treatments in the temperature range from 450 to 700 °C [16]. Unlike the lightinduced degradation in FZ silicon which was mainly identified in p-type material (except that a recent study observed a weak degradation in 200 Ω•cm n-type FZ silicon [17]), these thermally activated defects can have a substantial impact in both n-type and p-type FZ silicon [16], [18]. After formation, these defects can be permanently annihilated by an annealing at temperature above 1000 °C for 30 mins.…”
Section: Introductionmentioning
confidence: 88%
“…[16], this dependence on the equilibrium could also explain findings, where a lower LeTID extent was observed on wafers with lower doping concentration. [26] Considering the temporary recovery, B-H pairs would need to dissociate, with the dissociated hydrogen binding to LD to form the recombination-inactive LP. Even though, on a fundamental level, a complex dissociates more likely with increasing temperature, the important factor for this reverse reaction is the concentration of H þ .…”
Section: Implications On Letid Defect Formationmentioning
confidence: 99%